Nutrition in Renal Supportive Care: Patient‐driven and flexible. Issue 10 (October 2017) - Stevenson, Jessica; Meade, Anthony; Randall, Ann‐Maree; Manley, Karen; Notaras, Stephanie; Heaney, Susan; Chan, Maria; Smyth, Alison; Josland, Elizabeth; Brennan, Frank Patrick; Brown, Mark A
Abstract: Renal Supportive Care is an alternative treatment pathway in advanced chronic kidney disease that is being increasingly adopted, particularly in the elderly. Renal Supportive Care uses principles of palliative care and has been developed to enhance the care for dialysis patients with a high symptom burden and those being managed on a non‐dialysis pathway. Nutrition management is often an under‐recognized component of care and can play an important role in improving patients' quality of life to reduce symptom burden, support physical function and independence and provide appropriate counselling to patients and their families to ensure the goals of Renal Supportive Care are met. Nutrition interventions need to target patient and treatment goals, with frequent monitoring to ensure patient needs are being met. This review outlines available literature on this topic and suggests some practical ways in which nutrition can be enhanced for these patients. Summary at a Glance: The present review discusses the nutritional aspects of Renal Supportive Care (RSC) in terminally ill end‐stage renal disease patients (ESRD) focusing on high symptom burden patients and those with end‐stage renal disease being managed without dialysis.